Detection of Particle Concentration and Particle Size Based on Aerodynamic Particle Size Spectrometer. (24th August 2022) - Zhang, Jingxiu; Zhang, Zhiwei; Hou, Longfei
Abstract : In order to solve the problem of the continuous online monitoring of the fixed pollution source emission particles, on the basis of the advantages and disadvantages of the comprehensive analysis of the extinction method, the β -ray absorption method, the micro-oscillating balance method, the charge transfer method, and the light scattering method, the particle size distribution and concentration optical detection system based on aerodynamic particle size spectrometer is designed according to the Mie light scattering principle. A high-performance aerodynamic particle size spectrometer is designed using a single-wavelength method to measure the concentration of particulate matter, and the equipment and the detection system are used in the continuous monitoring of particulate matter emitted by thermal power plants and compared with the ES632 equipment. Through the system test, the results show that compared with the ES632 equipment performance, the lowest concentration measured by the design of aerodynamic particle size spectrometer equipment can reach 0.1 mg/m 3 with a measurement accuracy of 0.01 mg/m 3 . Compared with the ES632 equipment, the measurement concentration value is 8% higher, which meets the test requirements.